5.2: Solving Systems of Equations using Substitution

Slides:



Advertisements
Similar presentations
8-2: Solving Systems of Equations using Substitution
Advertisements

The student will be able to:
y=3x Find y if x=3 2. Find y if x= -2
Solve by graphing: y = -7x + 2 x + 4y = 8 (0,2). Objective: To use the substitution method to solve systems of linear equations.
4.3 Systems of Equations - Elimination Objective: The student will be able to: Solve systems of equations using elimination with addition and subtraction.
The student will be able to:
Objective The student will be able to: solve systems of equations using substitution. December 3, 2014.
1.2 Solving Linear Systems by Substitution 9/19/12.
Substitution Method: 1. Solve the following system of equations by substitution. Step 1 is already completed. Step 2:Substitute x+3 into 2 nd equation.
Objective The student will be able to: solve systems of equations using substitution. SOL: A.9.
Objective The student will be able to: solve systems of equations using substitution (including special cases in which lines are parallel or coinciding)
Solving Systems of Equations using Elimination. Solving a system of equations by elimination using multiplication. Step 1: Put the equations in Standard.
 What is the slope of the line that passes through the following points. 1.(-2, 5) (1, 4)  Identify the slope and y -intercept of each equation. 2.y.
Dr. Fowler CCM Solving Systems of Equations By Substitution – Harder.
Solving Systems of Equations By Substitution – Easier
Solving Systems of Linear Equations by Substitution; Applications Solve systems of linear equations using substitution. 2.Solve applications involving.
Solving Linear Systems of Equations by Substitution Section 3.2, Part I.
Solving Systems of Equations So far, we have solved systems using graphing and substitution. These notes show how to solve the system algebraically using.
3-2 Solving Systems Algebraically. In addition to graphing, which we looked at earlier, we will explore two other methods of solving systems of equations.
Solving Systems by Substitution (isolated) Solving Systems by Substitution (not isolated)
Objective The student will be able to: solve systems of equations using elimination with addition and subtraction.
7.2 Solving Systems Using Substitution. 7.2 – Solving Syst. By Subst. Goal / “I can…” Solve systems using substitution.
Solving Systems of Equation Using Subsitution Lesson 6-2 Oct. 24, 2014.
Algebra 1 Review Systems of Linear Equations Using Substitution
Objective I can solve systems of equations using elimination with addition and subtraction.
The student will be able to:
Solving Systems of Equations using Substitution
Solving Systems of Equations
Warm Up x = y – 3 9 – 3x 12 9 Simplify each expression.
Solving Systems of Equations with Substitution
The student will be able to:
3-2: Solving Systems of Equations using Substitution
Math 1201-Unit:7 Systems of Linear equations
The student will be able to:
Solve a system of linear equation in two variables
The student will be able to:
The student will be able to:
The student will be able to:
SYSTMES OF EQUATIONS SUBSTITUTION.
3-2: Solving Systems of Equations using Substitution
Solving Systems of Equations using Substitution
The student will be able to:
The student will be able to:
The student will be able to:
3-2: Solving Systems of Equations using Substitution
The student will be able to:
The student will be able to:
The student will be able to:
Maintenance Sheet 18 Due Tomorrow
The student will be able to:
Solving Systems of Equations
If you can easily isolate one of the variables,
Question How do you solve a system of simultaneous equations by substitution?
Systems of Equations.
Solving Systems of Equations
Warm-Up Solve the system by graphing..
The student will be able to:
The student will be able to:
3-2: Solving Systems of Equations using Substitution
Solving Systems of Equations
The student will be able to:
Solving Systems by Substitution
The student will be able to:
3-2: Solving Systems of Equations using Substitution
3-2: Solving Systems of Equations using Substitution
The student will be able to:
The student will be able to:
3-2: Solving Systems of Equations using Substitution
3-2: Solving Systems of Equations using Substitution
The student will be able to:
Presentation transcript:

5.2: Solving Systems of Equations using Substitution

Solving Systems of Equations using Substitution Steps: 1. Solve one equation for one variable (y= ; x= ; a=) 2. Substitute the expression from step one into the other equation, and SOLVE. 3. Substitute back into the equation we solved for in Step 1, and SOLVE 4. Check the solution in both equations of the system.

Example #1: y = 4x 3x + y = -21 Step 1: Solve one equation for one variable. y = 4x (This equation is already solved for y.) Step 2: Substitute the expression from step one into the other equation. 3x + y = -21 3x + 4x = -21 7x = -21 x = -3

y = 4x 3x + y = -21 Step 4: Substitute back into either original equation to find the value of the other variable. y = 4x = 4 (-3) y = -12 Solution to the system is (-3, -12).

y = 4x 3x + y = -21 3x + y = -21 y = 4x 3(-3) + (-12) = -21 Step 5: Check the solution in both equations. Solution to the system is (-3,-12). 3x + y = -21 3(-3) + (-12) = -21 -9 + (-12) = -21 -21= -21 y = 4x -12 = 4(-3) -12 = -12

Example #2: x + y = 10 y = -x +10 5x - y = 2 5x -(-x +10) = 2 Step 1: Solve one equation for one variable. x + y = 10 y = -x +10 Step 2: Substitute the expression from step one into the other equation. 5x - y = 2 5x -(-x +10) = 2

5x -(-x + 10) = 2 5x + x -10 = 2 6x -10 = 2 6x = 12 x = 2 x + y = 10 Simplify!! 5x -(-x + 10) = 2 5x + x -10 = 2 6x -10 = 2 6x = 12 x = 2

Solution to the system is (2,8). x + y = 10 5x – y = 2 Step 4: Substitute back into the equation we solved for in step 1 y = -x + 10 = -(2) + 10 y = 8 Solution to the system is (2,8).

5x – y = 2 x + y =10 5(2) - (8) = 2 2 + 8 =10 10 – 8 = 2 10 =10 2 = 2 Step 5: Check the solution in both equations. Solution to the system is (2, 8). 5x – y = 2 5(2) - (8) = 2 10 – 8 = 2 2 = 2 x + y =10 2 + 8 =10 10 =10

Solving a system of equations by substitution Pick the easier equation. The goal is to get y= ; x= ; a= ; etc. Step 1: Solve an equation for one variable. Step 2: Substitute Put the equation solved in Step 1 into the other equation. Substitute the value of the variable into the equation. Step 3: Plug back in to find the other variable. Step 4: Check your solution. Substitute your ordered pair into BOTH equations.

1) Solve the system using substitution x + y = 5 y = 3 + x Step 1: Solve an equation for one variable. The second equation is already solved for y! Step 2: Substitute x + y = 5 x + (3 + x) = 5 2x + 3 = 5 2x = 2 x = 1

1) Solve the system using substitution x + y = 5 y = 3 + x x + y = 5 (1) + y = 5 y = 4 Step 3: Plug back in to find the other variable. (1, 4) (1) + (4) = 5 (4) = 3 + (1) Step 4: Check your solution. The solution is (1, 4). What do you think the answer would be if you graphed the two equations?

Which answer checks correctly? 3x – y = 4 x = 4y - 17 (2, 2) (5, 3) (3, 5) (3, -5)

2) Solve the system using substitution 3y + x = 7 4x – 2y = 0 It is easiest to solve the first equation for x. 3y + x = 7 -3y -3y x = -3y + 7 Step 1: Solve an equation for one variable. Step 2: Substitute 4x – 2y = 0 4(-3y + 7) – 2y = 0

2) Solve the system using substitution 3y + x = 7 4x – 2y = 0 -12y + 28 – 2y = 0 -14y + 28 = 0 -14y = -28 y = 2 4x – 2y = 0 4x – 2(2) = 0 4x – 4 = 0 4x = 4 x = 1 Step 3: Plug back in to find the other variable.

2) Solve the system using substitution 3y + x = 7 4x – 2y = 0 Step 4: Check your solution. (1, 2) 3(2) + (1) = 7 4(1) – 2(2) = 0 When is solving systems by substitution easier to do than graphing? When only one of the equations has a variable already isolated (like in example #1).

2x + 4y = 4 3x + 2y = 22 -4y + 4 -2y + 2 -2x + 4 -2y+ 22 If you solved the first equation for x, what would be substituted into the bottom equation. 2x + 4y = 4 3x + 2y = 22 -4y + 4 -2y + 2 -2x + 4 -2y+ 22

3) Solve the system using substitution x = 3 – y x + y = 7 Step 1: Solve an equation for one variable. The first equation is already solved for x! Step 2: Substitute x + y = 7 (3 – y) + y = 7 3 = 7 The variables were eliminated!! This is a special case. Does 3 = 7? FALSE! When the result is FALSE, the answer is NO SOLUTIONS.

3) Solve the system using substitution 2x + y = 4 4x + 2y = 8 Step 1: Solve an equation for one variable. The first equation is easiest to solved for y! y = -2x + 4 4x + 2y = 8 4x + 2(-2x + 4) = 8 Step 2: Substitute 4x – 4x + 8 = 8 8 = 8 This is also a special case. Does 8 = 8? TRUE! When the result is TRUE, the answer is INFINITELY MANY SOLUTIONS.